2021
DOI: 10.3390/jcs5020055
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Molecular Dynamics Simulations for Elucidating Fine Structural, Physico-Chemical and Thermomechanical Properties of Lignocellulosic Systems: Historical and Future Perspectives

Abstract: The use of Molecular Dynamics (MD) simulations for predicting subtle structural, thermomechanical and related characteristics of lignocellulosic systems is studied. A historical perspective and the current state of the art are discussed. The use of parameterised MD force fields, scaling up simulations via high performance computing and intrinsic molecular mechanisms influencing the mechanical, thermal and chemical characteristics of lignocellulosic systems and how these can be predicted and modelled using MD i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
(330 reference statements)
0
2
0
Order By: Relevance
“…After that, the X and Y coordinates were selected, and the grain's form and size were calculated [35]. Between the grains, almost 2 Å space was generated.…”
Section: Generation Of Modelmentioning
confidence: 99%
“…After that, the X and Y coordinates were selected, and the grain's form and size were calculated [35]. Between the grains, almost 2 Å space was generated.…”
Section: Generation Of Modelmentioning
confidence: 99%
“…To solve such kind of issue, understanding the microstructure of lignin in an overall hydrophobic medium such as asphalt mixture in molecular detail is necessary. Up to now, there have been relatively few computational studies of lignin on its structure, dynamics, and functions. , With the development of the Chemistry at Harvard Macromolecular Mechanics (CHARMM) empirical molecular mechanics force field for lignin, it provides an important route for studying lignin through molecular dynamics simulation . Running all-atom simulations using the CHARMM force field, Petridis and Smith found that low-molecular-weight lignin polymer (mainly made from G units with different chain lengths) adopts collapsed conformations in water at both room temperature and 500 K .…”
Section: Introductionmentioning
confidence: 99%